(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Polycystic ovary syndrome (PCOS) is a common hormonal disorder affecting women of reproductive age. It is characterized by irregular periods, excess androgen levels, and polycystic ovaries, often leading to fertility issues and metabolic complications Aim of Study: To compare the ultrasound features of polycystic ovaries between obese and non-obese patients. Methodology: A prospective observational design was conducted at Gilani Ultrasound Center in Lahore. A total of 100 participants were included using a non-probability purposive sampling technique. Data collection spanned a period of 9 months. The study included females of all ages, categorized into four groups: obese with PCOS, obese without PCOS, non-obese with PCOS, and non-obese without PCOS. Exclusion criteria encompassed females with treated PCOS, those undergoing infertility treatment, individuals with congenital anomalies, and those with ovarian abnormalities other than PCOS. Results: This study on polycystic ovary syndrome (PCOS) included 126 participants with a mean age of 28.7 ± 4.6 years, of whom 66.7% were diagnosed with polycystic ovaries. The mean body mass index (BMI) was 27.6 ± 5.1, with a significant association found between PCOS and obesity (p = 0.01). Mean ovarian volumes were similar for both ovaries (left: 16.452 ± 8.2930 cm³; right: 16.573 ± 8.2358 cm³), which are higher than previously reported values. Clinically, PCOS was significantly associated with a string-like appearance of the ovaries (p < 0.001), diabetes (p = 0.040), hypertension (p = 0.040), amenorrhea (p < 0.001), and infertility (p = 0.02). Hormonal analyses showed significant links with thyroid dysfunction, progesterone, luteinizing hormone (LH), testosterone, and follicle-stimulating hormone (FSH). Conclusion: These findings underscore the complex nature of PCOS and its associations with metabolic and hormonal disturbances, highlighting the need for a comprehensive approach to diagnosis and management.